Injuries of children and adolescents in home and school environments - Vitošová, Andrea; Průchová, Dominika (Journal of Nursing, Social Studies and Public Health, 2010)
In view of the current lack of epidemiological data with detailed information and analysis of the causes of injuries in the home and school environments, a study of children's injuries is being conducted in the South-Bohemian administrative region. The study aims to analyse injuries of children age 0–18, including the most frequent injury locations, mechanisms and other factors relevant to the occurrence of injuries. Data on children who sought medical treatment of injuries during the period from October 2009 to September 2010 were collected by engaging general practitioners for children and adolescents. A total of 568 completed questionnaires entitled “Child injury/intoxication” were collected during the study period; 220 questionnaires included information regarding injuries in home environments and 87 questionnaires included information regarding injuries in school environments. The study results show that children 0–3 contribute a high fraction (40%) to injuries at home. Boys were involved to a higher extent (57%) than girls (43%). Injuries happened most frequently during plays (55%) in the garden (23%) or in the kitchen (19%). Surfaces were the immediate causes of the injuries frequently (29%). As to the injury mechanism, falls predominated (36%), causing open wounds in 33% cases. The upper limbs were injured in 33%. Mere 20% families had some safety devices in their homes such as furniture corner protectors or baby socket protectors. In the school settings, boys and girls are involved in injuries to a nearly identical extent: boys 51%, girls 49%. The most endangered age group is age 11–14 (37%). Impact was the most frequent (31%) mechanism of injury; the upper limbs were injured in 39% cases; bruises were in involved in 28% injuries; and 38% injuries happened in the gymnasium during classes (39%). Injuries occurred during sports activities in 49%; surfaces were the immediate dangerous objects in 38%; 6% injuries were classed as intentional. The causes, types, circumstances and other factors of injuries in the group of children that received medical treatment for injury during the study period did not differ from those reported in available literature.
Keywords: financování organizované; průzkumy a dotazníky; Female; Infant; Safety; dítě; předškolní dítě; ženské pohlaví; Surveys and Questionnaires; Adolescent; volnočasové aktivity; lidé; Accidents; Accidents, Home; rodiče; úrazy a nehody; úrazy v domácnosti; Leisure Activities; Parents; Risk Factors; Financing, Organized; Data Interpretation, Statistical; Male; kojenec; interpretace statistických dat; Child, Preschool; Athletic Injuries; rizikové faktory; bezpečnost; Accidental Falls; sportovní úrazy; Child; mužské pohlaví; úrazy pádem; mladiství; Humans